Pengaruh Etika Bisnis dan Moderasi Beragama Terhadap Peningkatan Perekonomian UMKM di Kota Mataram - Bayu Wijaya, I Gede (Universitas Islam Nahdlatul Ulama Jepara, 2025)
Business actors are required to maintain a positive image in their operations. By doing so, they can outperform competitors and ensure their business continues to run smoothly. Facing intense competition, it is undeniable that some business actors may engage in less positive practices. Business ethics are essential to create a healthy competitive climate. With business ethics, business actors can engage in good practices and avoid unethical behavior, allowing them to compete fairly. The purpose of this study is to determine the extent of the influence of business ethics variables on improving the economy of MSMEs in Mataram. The research method used is quantitative, with the assistance of SPSS calculations, and data was collected from questionnaires distributed to 84 respondents as samples. The conclusion of the study indicates that the business ethics variable has a significant influence on the improvement of the MSME economy. The limitations of this study are due to available resources, so the research was conducted only on MSME actors in Mataram